Dealing with Emotions and Feelings through Reading and Writing: A Commitment with Mental Health Care (2022)
This paper stands for the idea of social responsibility that someone who teaches has. Having the aim of not separating the human being as an emotional subject from academic training, the researcher proposes the integration of emotions and feelings into the curriculum as a tool to promote mental health care. Such integration has two components: a linguistic component and a psychological component, that seek to strengthen the linguistic abilities while simultaneously taking care of mental health, specifically emotional intelligence abilities. As a result, it was found that students, ages thirteen to seventeen years old, were able to read critically and generate debate with the purpose of creating a constructed critical thinking related to their emotions that also produced texts that not only helped them to develop abilities in reading and writing but also made them more aware of their emotions. Keywords: Mental health, emotional intelligence, reading, writing, experimental research